Te tohu-a-Tuu = The sign of Tuu : a study of the warrior arts of the Maori : a thesis presented in partial fulfillment of the requirements for the degree of Master of Philosophy in Maori Studies at Massey University - Reedy, Hirini George (Massey University, 1996)
The title "Te Tohu-a-Tuu (The Sign of Tuu)" is the name of a taiaha on-guard position that invokes Tuu, the Maori god of war. It has been chosen to reflect the subject of Maori warfare in the pre-European period. Maori warfare during this period was very much influenced by the cosmological and environmental beliefs of the Maori. These beliefs were mainly articulated through the oral histories of the Maori. Accounts of pre-European Maori warfare has mainly been written by early European historians who were greatly influenced by the prevailing social customs and intellectual thinking of the time. No linkage was made between the Maori protocols and processes of warfare with the cosmological and environmental beliefs practiced by the Maori. As a result the current understanding of Maori warfare has largely stemmed from written accounts by non-Maori. This thesis explores Maori warfare through the institution of Tuumatauenga, the ugly faced Maori god of war. It will show the processes and the protocols that the Maori warrior used to prepare the mind and body for war and battle in the pre-European period. This preparation often started in the womb and progressed from early childhood through to initiation, as a youth, into the schools of war. From here the student graduated on to the battle-field as a toa taua or warrior. Through personal prowess and skill at arms, the toa taua gained Ika-a-Whiro or war leadership status. The institution of Tuumatauenga is then linked with other Maori gods to show that Maori warfare and warrior arts were greatly influenced by cosmological and environmental beliefs.
Keywords: Maori (New Zealand people); Warfare; Pakanga; Te Ao Tāwhito; Mau rākau; Atua; Māori Masters Thesis